TRANSFORMATIONAL LEADERSHIP AND ITS EFFECT ON SCHOOL CLIMATE IN MERU SOUTH SUBCOUNTY-THARAKA NITHI COUNTY - MUTHONI, NYAGAH, CAROLINE; Kathuri, Prof. N. J.; Kibaara, Dr. T. M. (IJRDO- Journal of Educational Research, 2018)
Leadership is an essential facet for the development of an organization. School leadership therefore, plays a vital role in the development and achievement of school objectives and the goals of an education system as a whole. Transformational leadership has been described as inspiring leadership that creates an environment of trust, hope and motivation in schools. This study sought to determine the effect of transformational leadership style on school climate. The objectives of the study were to determine the effects of idealized influence on school climate, to establish the effects of inspirational motivation on school climate and to examine the effect of intellectual stimulation on school climate. The study was carried out in Meru South Sub County, Tharaka Nithi County which has shown persistent poor performance, coupled with indiscipline among students. The researcher adopted the descriptive survey design. The target population was 54 secondary school principals, 432 teachers and 12562 students in Meru South Sub County. A sample of 16 principals was selected using purposive sampling, while 130 teachers and 100 students were selected using both stratified and simple random sampling techniques. Data was collected using structured questionnaires. A pilot study was carried out using test re-test method to determine the reliability and the validity of the research instruments. Data was collected from teachers and students with the use of self-administered questionnaires, while the principals were interviewed face to face by the researcher. Data was analyzed using descriptive statistics with the help of Statistical Package for Social Sciences (SPSS) version 20.